EFFECT OF SECANG WOOD EXTRACT ON THE HISPATHOLOGICAL PICTURE OF THE HEART OF THE MALE MICE AFTER EXPOSURE TO CONVENTIONAL CIGARETTE SMOKE - Chandra, Franky Samuel Milenyano; Berata, I Ketut; Merdana, I Made (Buletin Veteriner Udayana, 2023)
Exposure to cigarette smoke can increase the risk of coronary heart disease due to the free radicals generated. One of the plants in Indonesia that contains antioxidants is sappan wood. The purpose of this study was to determine the effect of giving secang wood extract (Caesalpinia sappan Linn) on the histopathological picture of male mice (Mus musculus) after exposure to conventional cigarette smoke. This study used 24 samples of adult male mice aged 35-45 days with body weight between 30-35 grams obtained from a mouse farm in Gianyar, Bali. The sample was divided into 4 treatments with 6 replications, namely negative control without sappan extract treatment and exposure to cigarette smoke, positive control with 2 cigarette smoke exposure a day, 2 cigarette smoke exposure a day and 30 mg/head dose of sappan wood extract. and the treatment was exposed to cigarette smoke as much as 2 cigarettes a day and administration of sappan wood extract at a dose of 60 mg/head, for 30 days. On the 31st day, the experimental animals were sacrificed to take heart muscle and processed into histopathological preparations. The examination was carried out based on the presence of congestion and inflammation lesions. The severity of the lesions was scored as mild, moderate and severe. Observational data were analyzed using the Kruskal-Wallis non-parametric statistical test and continued with the Mann-Whitney test if there was a significant difference. The results showed that there was a significant difference (p<0.05) between mice exposed to cigarette smoke and mice given sappan wood extract after exposure to cigarette smoke. It can be concluded that the administration of sappan wood extract at a dose of 30mg/mouse and 60mg/mouse can improve the heart lesions of male mice after exposure to conventional cigarette smoke. Further research is needed on the use of sappan wood extract with different doses in order to obtain more comprehensive results in treating heart damage after exposure to cigarette smoke.